2013
DOI: 10.1111/jog.12131
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of massive congenital bilateral chylothorax in a hydropic fetus with true mosaicism 47,XXX/46,XX

Abstract: Fetal congenital chylothorax is a rare condition that occurs sporadically or can be associated with abnormal karyotype or structural chromosomal anomalies. We report a unique case of fetal congenital bilateral chylothorax associated with mosaicism 47,XXX/46,XX. A female fetus affected by massive bilateral hydrothorax and ascites was diagnosed at 34(+1) weeks of gestation. Previous ultrasonographic exams were completely normal. Immune causes of hydrops were excluded. Elective cesarean section was performed soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results of the review are shown in Table 1. In our review, we identified three cases of fetal hydrops associated with 47,XXX [7][8][9]. In cases 2 and 3, chromosome testing was conducted owing to an advanced maternal age, and a 47,XXX karyotype was found.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the review are shown in Table 1. In our review, we identified three cases of fetal hydrops associated with 47,XXX [7][8][9]. In cases 2 and 3, chromosome testing was conducted owing to an advanced maternal age, and a 47,XXX karyotype was found.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing to complete 47, XXX, clinical symptoms of individuals with 46, XX/47, XXX mosaicism are less severe and expectations of their outcomes are better[5]. Still, there are reports on severe symptoms of 46, XX/47, XXX mosaicism including autoimmune myelo brosis, congenital chylothorax and azoospermia[18][19][20].…”
mentioning
confidence: 99%